PEMBINAAN BAHASA DAN SASTRA: PEMANFAATAN MEDIA DIGITAL SEBAGAI UPAYA PENINGKATAN LITERASI DI KELURAHAN PULOKERTO, SUMATERA SELATAN - Shelly Aulia Ramadhanti; Muhammad Fitrah Mahaini (Yayasan Literasi Sains Indonesia, 2022)
The technology of information and communication has developed and affects various sectors of life, including the education. The level of literacy is also the main indicator that affects education in a country. The use of digital media, including instant messaging applications such as WhatsApp, can be used as a learning platform for literacy. The study was conducted using the Participatory Action Research method to 5 families in Pulo Kerto Village, Palembang City. Researchers use WhatsApp Business and Interactive Chatterbot services as a media of coaching about language and local literature. The results of this study indicate that the activity was effective and there was a progressive increase in participants' understanding of language and literature material, which was 237.5%. It is hoped that this research can be continued by using a larger sample so that it can provide more optimal results in the form of increasing the literacy skills.